The “Egyptian Saints” of the Abyssinian Hagiography - Marrassini, Paolo (Aethiopica, 2005)
It seems possible to isolate a group of saints born in Egypt (or living there for a long time), different from the traditional saints of that country mainly because they were not martyrs, and substituted the martyrdom by penances and absolute asceticism; the presence of the desert is much more pronounced than in the rest of Abyssinian hagiography, and nearly absolute; the activity of the devil is also very heavily marked; almost all of them are of “Roman” birth or connection. They are Bula/Abib, Gabra Krestos/Alexius, Latṣun, Nob, Gabra Manfas Qeddus, John the Oriental, maybe Tadēwos of Dabra Bartarwa, Yoḥanni of Däbrä ʿAśa, and some others, to which the “Aksumite” saints must be added. The relationship of these saints among themselves is also demonstrated by the codices, in which the “Life” or the hymnography pertaining to one or more of them occur together with those of some of the others, in different combinations.